Consumo de antibióticos, fatores de risco e evolução de pneumonia associada à ventilação por Staphylococcus aureus sensível ou resistente à oxacilina em pacientes internados na Unidade de Terapia Intensiva de Adultos de um hospital universitário brasileiro - Moreira, Michel Rodrigues (2008)
The VAPs associated with antibiotics multi-resistant bacteria characterize themselves by higher morbidity, mortality and costs. The aim of this study was to evaluate epidemiological differences among resistant (ORSA) and sensible (OSSA) S. aureus to oxacillin VAPs, as well as its prognostic when of the empirical antimicrobial therapeutic, beyond the relationship between the antibiotic consumption of carbapenems, 3rd and 4th-generations cephalosporins, vancomycin and the etiology multi-resistant microorganisms VAPs in patients in a mixing ICU of adults. A prospective control (10)-case (13) study was conducted. Cases of VAP caused by these phenotypes (ORSA and OSSA) in 23 patients were carried out from May 2006 to April 2007. VAPs were defined based on clinical, when its onset occurred after 48 hours of mechanical ventilation, radiological and microbiological ( 106 CFU/ml count in the tracheal aspirate) criteria. A total antibiotic usage density was determined and stratified by group of antimicrobial agents. Resistance rates profile was defined in vitro by the diffusion in gel technique. Altogether 53 cases of VAPs were diagnosed. S. aureus pneumonia was observed in 23 cases, 53.5% and 43.5%, respectively, by ORSA and OSSA, predominant in late-onset VAPs with frequencies of 92.3% and 60.0%, respectively. Age > 60 was the only risk factor for VAP by ORSA (P<0.05). Mortality rate was higher (P>0.05) in this group with 38.5% versus 20.0% in the group with OSSA, although the inadequate antibiotic therapy in the group with pneumonia by ORSA was lower (P>0.05) than that observed in the cases of VAP by OSSA (23.1% versus 30.0%). The two most frequent pathogens isolated in the participating patients were P. aeruginosa (40.0%) and S. aureus (38.3%) with about 2/3 of the samples resistant to imipenem and oxacylin, respectively. The consumption of 3rd and 4th-generations cephalosporins (496.9 DDDs/1.000 patient-days) was highest and associated with the increase in the incidence of VAPs by P. aeruginosa and S. aureus, as well as by resistance to antibiotics phenotypes. The prescribing of vancomycin and carbapenems (143.0 and 184.3 DDDs/1.000 patient-days) were proportionally lower and the latter linked with higher P. aeruginosa rates. S. aureus was the second agent of VAPs with 56,5% of cases by ORSA, associated with age, late-onset VAP, use of corticoids and antibiotics and hospitalization time > 8 days. Although statistically significant differences were not observed, there was a worse prognostic in the cases of VAPs by this phenotype, and a relationship with the prescription of some antibiotics and the etiology higher than 50% of multi-resistant microorganisms.